Blunting of insulin inhibition of proteolysis in legs of older subjects may contribute to age-related sarcopenia - Wilkes, Emilie A; Selby, Anna L; Atherton, Philip J; Patel, Rekha; Rankin, Debbie; Smith, Ken; Rennie, Michael J (The American journal of clinical nutrition, 2009)
Reduced postprandial muscle proteolysis is mainly due to increased insulin availability. Whether rates of proteolysis in response to low physiologic doses of insulin are affected by aging is unknown. We tested the hypothesis that suppression of leg protein breakdown (LPB) by insulin is blunted in older subjects, together with blunted activation of Akt-protein kinase B (PKB). Groups of 8 young [mean (+/-SD) age: 24.5 +/- 1.8 y] and older (65.0 +/- 1.3 y) participants were studied during euglycemic (5 mmol/L), isoaminoacidemic (blood leucine approximately 120 micromol/L) clamp procedures at plasma insulin concentrations of approximately 5 and approximately 15 microIU/mL for 1.5 h. Leg amino acid balance, whole-leg protein turnover (as dilution of amino acid tracers), and muscle protein synthesis were measured with D(5)-phenylalanine and [1,2-(13)C(2)]leucine. The kinase activity of muscle Akt-PKB and the extent of phosphorylation of signaling proteins associated with the mTOR (mammalian target of rapamycin) pathway were measured before and after the clamp procedures. Basal LPB rates were not different between groups (66 +/- 11 compared with 51 +/- 10 nmol leucine x 100 mL leg(-1) x min(-1) and 30 +/- 5 compared with 24 +/- 4 nmol phenylalanine x 100 mL leg(-1) x min(-1) in young and older groups, respectively). However, although insulin at approximately 15 microIU/mL lowered LPB by 47% in the young subjects (P < 0.05) and abolished the negative leg amino acid balance, this caused only a 12% fall (P > 0.05) in the older group. Akt-PKB activity mirrored decreases in LPB. No differences were seen in muscle protein synthesis or associated anabolic signaling phosphoproteins. At moderate availability, the effect of insulin on LPB is diminished in older human beings, and this effect may be mediated through blunted Akt-PKB activation.